1997
DOI: 10.1007/bf03161983
|View full text |Cite
|
Sign up to set email alerts
|

The1HT 1 study of the influence of clay addition on Portland cement hydration

Abstract: Effects of addition of three standard clay minerals, Na-montmorillonite, illite and kaolinite, on Portland cement hydration properties were studied. The IH spin-lattiee relaxation of exchangeable water was monitored during hydration time and the data were processed by spin-grouping analysis. The values and evolution dynamics of both resolved T l eomponents and corresponding magnetization fractions show that each day mineral lowers the fluidity of Portland cement paste and accelerates its hydration in dormant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For example, it has been observed that prolonged drying decreases the surface area [34,35]. Samples are dried prior to adsorption, e.g., by D-drying for periods as long as 3 weeks [17]. Rarick et al [35] found that the nitrogen surface area of Portland cement paste decreased with storage time after D-drying which they tentatively attributed to carbonation.…”
Section: Structural Changes Due To Drying and Storagementioning
confidence: 97%
See 1 more Smart Citation
“…For example, it has been observed that prolonged drying decreases the surface area [34,35]. Samples are dried prior to adsorption, e.g., by D-drying for periods as long as 3 weeks [17]. Rarick et al [35] found that the nitrogen surface area of Portland cement paste decreased with storage time after D-drying which they tentatively attributed to carbonation.…”
Section: Structural Changes Due To Drying and Storagementioning
confidence: 97%
“…Micro-or nano-sized layer silicates exhibit no pozzolanic reactions in Portland cement systems [15]. However, addition of these silicates to Portland cements accelerates the cement hydration [15][16][17] by increasing the degrees of hydration for both alite and belite [17]. Moreover, it has been shown that replacement of 20 wt.% of the Portland cement by a kaolinite or illitic clay results in an increased porosity of paste samples, but a decreased porosity of mortars as measured by mercury intrusion porosimetry [18].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the rate of breaking the Ca-O, Si-O-Si, and Al-O-Al bonds is sped up, which leads to the increase in Ca 2+ ion concentration and accelerates the formation of hydration products and the arrival of the initial setting state [20,46,47]. However, the water absorption of mud also delays the hydration process, especially with high kaolinite content [48][49][50][51], leading to a longer final setting time. As for the effect of the particle sizes of mud on setting time, the capability of liquid absorption of clay with a smaller particle size is stronger than that of silt with a larger particle size [46].…”
Section: Se Ing Timementioning
confidence: 99%
“…When the silt and clay content is less than 4%, the mud has almost no effect on the compressive and flexural strengths of AAS mortar, which is because the mud fills the pores of the sand skeleton [52] and reduces the negative effect caused by the addition of mud. When the mud content exceeds 4%, the compressive and flexural strengths of AAS mortar decrease rapidly, mainly for the following reasons: (1) mud absorbs water from the fresh mortar and this affects the hydration process [49][50][51];…”
Section: Mechanical Propertymentioning
confidence: 99%